The reality of archaeological monuments in Peru: a view from Tambo Viejo - Valdez, Lidio M. (2023)
In Peru, we have the privilege of having an enormous wealth of archaeological monuments that are scattered throughout the country. However, over time we have not managed how to make an effective use of this wealth, much less how to preserve it for future generations. Instead, we are passive observers of how archaeological monuments remains forgotten and neglected or are in effect swept away under the pretext of “development” and “progress.” Our unwritten history disappears before our eyes, and we have no will to even stop the destruction. The history of the archaeological site of Tambo Viejo in the Acari Valley that I discuss here is possibly also the history of many other archaeological monuments. With the reflection presented here, perhaps, it is possible to begin to reconsider and look for solutions that allow archaeological sites to be safeguarded. I am convinced that we can do more, and we should do more.